O Regimento dos preços dos medicamentos [...] na farmácia brasileira oitocentista - Peruchi, Amanda [UNESP] (Fundaco Oswaldo Cruz, 2020)
On November 5th, 1808, D. Joao de Braganca issued a license about the practice of druggists and the price of drugs and ordered the creation of a regulation to tax the cost of medicines marketed in Brazil. First published on 1809, the Regimento dos precos dos medicamentos... gained new editions in the following years and became an indispensable working tool for those involved in the making and trading of drugs at this time. This paper situates historically and sheds light on a document briefly explored by the researchers of the history of the Brazilian pharmacy, taking into account that it was one of the first initiatives of the Luso-Brazilian government in line with the pharmaceutical activity in Brazil in the nineteenth century.
Regulation of drug prices in nineteenth-century Bazilian pharmacy
Keywords: pharmacy history; drugs; Brazil; XIX century